2005
DOI: 10.1080/02699050500309510
|View full text |Cite
|
Sign up to set email alerts
|

A profile of community navigation in adults with chronic cognitive impairments

Abstract: The results of both studies were consistent and indicated that community access is severely restricted for individuals with CI. The majority of trips that were taken tended to be routine and assisted. The variety of travel was limited; participants ventured to the same set places with the same people. Participants described barriers accounting for these problems and suggested a number of strategies to minimize problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…However, the data from the paratransit dispatch centre may also not fully represent the complete spectrum of transportation challenges since data were recorded by dispatchers receiving information from drivers in the field. For example, previous research has documented that individuals with cognitive impairments also demonstrate challenges with navigating to and within their destination [10,11], but these data were not available in the current study.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, the data from the paratransit dispatch centre may also not fully represent the complete spectrum of transportation challenges since data were recorded by dispatchers receiving information from drivers in the field. For example, previous research has documented that individuals with cognitive impairments also demonstrate challenges with navigating to and within their destination [10,11], but these data were not available in the current study.…”
Section: Discussionmentioning
confidence: 77%
“…It was challenging to collect sufficient data for trip observations specifically for TBI survivors who present with navigation challenges because they either did not use public transportation or did not frequently venture outside their residences. Sohlberg et al [10] previously demonstrated that these individuals are primarily 'home-bound' despite adequate physical ability and availability of an accessible and reliable bus route at their door-step. Anxiety, fear of getting lost or leaving an established 'comfort zone', financial restrictions, reduced initiation or spontaneity, and lack of opportunity precluded many of these individuals from venturing out.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the barriers and challenges of using alternative transport have been reported in several studies (Risser, Iwarsson, & Ståhl, 2012;Rosenkvist, Risser, Iwarsson, Wendel, & Ståhl, 2009;Sohlberg, Todis, Fickas, Hung, & Lemoncello, 2005). Transportation services, which include public transport and specialised services for persons with disability, have been perceived as unreliable, unpredictable and difficult to access (Ing, Vento, Nakagawa, & Linton, 2014;Rudman, Hebert, & Reid, 2006).…”
Section: Abi and Drivingmentioning
confidence: 99%